(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Groundwater is of significant importance for the preservation of life on Earth. The accurate estimation of the surface recharge is the secret to knowing and forecasting the capacity of the groundwater reservoir. The key aim of this work was to determine the soil regeneration of the river Ergene and its control variables. In order to classify spatially dispersed groundwater recharges and other water budget components, a grid-based water balance model was implemented which relates to hydroclimatic variables, land use, vegetation, geology and area relief studied.